Atrial fibrillation in patients with very high risk for stroke and adverse events: insights from the observational ARENA study - Alonso, Angelika; Akın, Ibrahim; Hochadel, Matthias; Borggrefe, Martin; Lesch, Hendrik; Grau, Armin J.; Zahn, Ralf; Lugenbiel, Patrick; Schwarzbach, Christopher Jan; Süselbeck, Tim; Senges, Jochen; Fastner, Christian (Journal of Clinical Medicine, 2024)
Background: Atrial fibrillation (AF) is a major cause of stroke. An individual risk estimation remains challenging, as AF patients with and without cerebrovascular event (CVE) may differ in yet unknown factors beyond those covered by the CHA2DS2-VASc score. We aimed to identify differences between AF patients with and without CVE with regard to AF characteristics and treatment, vascular risk factors and comorbidities, prognosis and outcome. Methods: We analyzed patients included in the Atrial Fibrillation Rhine-Neckar Region (ARENA) Project, an observational cohort study of patients with AF. Patients were recruited by their general practitioner or during a hospital stay and were divided into two groups for the present analysis: patients with acute CVE at baseline and/or history of CVE versus patients without CVE. Follow-up at 1 year was conducted via phone call. Results: Of 2061 included patients (60.6% male), 292 (14.2%) belonged to the CVE group. Patients in the CVE group were older (mean age 74.6 versus 71.7 years; p < 0.001) and had a higher CHA2DS2-VASc score at baseline (5.3 versus 3.3 points; p < 0.001) based on the preceding CVE. Moreover, patients with either acute or chronic CVE had a larger left atrium (median diameter 47/46 mm versus 44 mm; p = 0.001). Patients with acute CVE had structural heart diseases (p < 0.001) less frequently than patients with previous or without CVE. Mortality at 1 year (HR 1.95; 95%-CI 1.37-2.78) was more frequent in the CVE group (p < 0.001). During 1-year of follow-up, stroke occurred more frequently in survivors with CVE (2.9% versus 0%; p < 0.001). Conclusions: AF patients with CVE have a significantly worse prognosis than AF patients without CVE. Atrial structural remodeling, underlying cardiovascular disease, stroke-induced heart injury and further unidentified factors may account for this finding. Characterization of AF patients including echocardiography to detect atrial structural remodeling may be helpful in risk stratification beyond classical scores.
Gesehen am 30.04.2025